Essential oils, phytochemicals and bioactivities of alpinia aquatica - Nissha Bharrathi Romes, 1984-; Hasnah Mohd. Sirat, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2016